Anatomical Development and Histochemical Study of Steril Ovule Melinjo (Gnetum gnemon L.) - Pamungkas, Wanda Aulia; Susanti, Siti (Fakultas Biologi Universitas Gadjah Mada, 2024)
In this section, the abstract must be written in English. Melinjo (Gnetum gnemon L.) is a plant that grows and spreads throughout Indonesia. This plant is widely cultivated because of its economic value. The purpose of this study was to determine the anatomical development of sterile melinjo ovule at the tip, middle and base of the female strobili and to determine the content of secondary metabolites in melinjo sterile ovule. The material used is sterile ovulum melinjo at the tip, middle and base of the female strobilus. In observing the anatomical development of sterile melinjo ovule, preparations were made using the paraffin method, single staining, and observed under a microscope. The anatomical data of the sterile ovule were analyzed descriptively. Observation of secondary metabolite content was carried out through histochemical tests, then observed with a light microscope and the results of the observations were documented using OptiLab. The results of observing anatomical development show that at different ages of melinjo sterile ovule there are structural differences in the constituent tissues. The results of observations on anatomical development show that at different ages the melinjo sterile ovule has structural differences in its constituent tissue, the more mature the melinjo sterile ovule, the constituent tissue is increasingly degraded. Histochemical test results showed that the sterile melinjo ovule contained secondary metabolites of phenols, flavonoids, terpenoids, tannins, and alkaloids.